Drawing Skills in Students with Mild Intellectual Disability - Keskinova, Angelka; Ramo Akgün, Nergis (İstanbul University-Cerrahpaşa, 2022)
Children’s drawings, as well as the development of the ability to draw, are developed under the influence of a number of developmental abilities. The purpose of this research is to assess the quality of drawing in students with intellectual disabilities and to assess the abilities that participate in the formation of drawing. In this research, the ACADIA-test has been used and conducted on two groups of respondents, the target group of 63 students with mild intellectual disabilities and the second group of 80 students with typical development. The 63 respondents from the first group were from third to eighth grade of primary school, which is from the age of 9 to 14, 5 students were from the first grade, 8 students from the fourth grade, 10 from the fifth grade, 13 from the sixth grade, 12 from the seventh, and 15 students from the eighth grade. Thirty-three of the respondents from this group were male and 30 students were female. The 80 respondents from the second group were from third to fifth grade, which is from the age of 9 to 11, 23 students were from the third grade, 30 students from the fourth, and 27 students from the fifth grade. The group consisted of 37 female and 43 male students. Also, the drawing skills of students with typical development were compared by the variables—gender and age. According to the obtained results, the intellectual disabilities negatively affect the development of skills necessary for artistic expression, 44.45% of students with intellectual disabilities showed a high standard deviation from the standard values. Problems with the ability to draw occur in a small number of students with typical development (5.8%), which indicates the possibility of specific learning problems in these students. The ability to draw does not depend on the gender of the students, but it develops in the early school period and is directly dependent on the calendar age of students with typical development.
Keywords: Art expression, drawing skills, intellectual disability, typical development